Optimized aqueous extraction conditions for maximal phenolics, flavonoids and antioxidant capacity from Artocarpus heterophyllus (jackfruit) leaves by response surface methodology (RSM) - Sayuti, Nor Hafiza; Kamarudin, 'Ammar Akram; Ab Razak, Nor Asma; Saad, Norazalina; Pak Dek, Mohd Sabri; Mohd Esa, Norhaizan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: There are numerous studies on the therapeutic properties of Artocarpus heterophyllus. However, studies on the aqueous extraction of A. heterophyllus leaves are limited. This present study was conducted to optimize the extraction conditions of A. heterophyllus leaves to yield the highest phenolic, flavonoids and antioxidant contents. Methods: Response surface methodology (RSM) was employed to obtain a higher phenolic extraction parameter(s) of A. heterophyllus leaves using Central Composite Design (CCD). The antioxidant activity was then determined via ABTS (2,29-azinobis (3 ethylbenzothiazoline-6-sulfonic acid)) and DPPH (2,2-Diphenyl-1-picrylhydrazyl) assay and analysis of the individual phenolics was performed by high performance liquid chromatography (HPLC). Results: The optimum extraction conditions with higher phenolics content and antioxidant activity was achieved at 81°C, 100 min and 40 mL/g sample with a good desirability value of 0.87. Under these optimized parameters, total phenolics and flavonoids were 174.48 ± 4.05 mg GAE/g sample and 21.44 ± 0.05 mg RE/g sample, respectively. Meanwhile, antioxidant activity via ABTS and DPPH assays were 90.88% ± 0.09 and 87.22% ± 0.62, respectively. Finally, under optimal extraction conditions revealed 4 compounds identified as chlorogenic acid, quercetin, rutin and kaempferol. Conclusion: The optimisation are promising to improve phenolic yield and antioxidant activity in A. heterophyllusleaves. It also proved that A. heterophyllus leaves can be used as an alternative natural antioxidant especially in medicinal applications since all identified compound possess significant biological activities for human health.